2019
DOI: 10.1590/010318138653439430941
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative English Language Learning: Some Reflections From Interactions Between Pairs

Abstract: The focus of this study is on the interactions five pairs of students had in order to carry out a collaborative writing activity. The research was conducted in a language school of Goiânia, in Goiás, Brazil, with ten EFL/ESL students, in 2015. The objectives of this investigation are: a) to observe and discuss the elements that stand out during the students' interactions; and b) to investigate these learners' perceptions of the experience. This study is grounded on sociocultural theory (DONATO, 1994; HALL, 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…However, a few participants felt that collaborative translation using Google Docs was time-consuming and sometimes technically challenging. Likewise, Sousa et al (2019) and Yu-Fen and Shan-Pi (2011) reported some difficulties in using Google Docs in peer feedback, like disagreements and lack of clear communication to resolve any problem. L. Wang et al (2017) concluded that the collaborative process was problematic when students had different levels of language competence and engagement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a few participants felt that collaborative translation using Google Docs was time-consuming and sometimes technically challenging. Likewise, Sousa et al (2019) and Yu-Fen and Shan-Pi (2011) reported some difficulties in using Google Docs in peer feedback, like disagreements and lack of clear communication to resolve any problem. L. Wang et al (2017) concluded that the collaborative process was problematic when students had different levels of language competence and engagement.…”
Section: Discussionmentioning
confidence: 99%
“…A plethora of studies have investigated students' engagement in collaborative tasks (Saeed & Al Qunayeer, 2020;Woodard & Babcock, 2014). For example, Sousa et al (2019) conducted a case study to determine the factors influencing students' interactions in a collaborative activity. They also explored students' perceptions of this experience.…”
Section: Students' Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…However, if the videos chosen contain difficulties related to some vocabulary and cultural knowledge, students may be demotivated (Prodromou, 1996) from the disturbance of understanding. Teachers could try to select materials appropriate for learners and offer help if needed [32][33][34][35][36][37].…”
Section: Evaluate and Reflect On New Materialsmentioning
confidence: 99%
“…Group dictation differs from traditional dictation in that the former entails collaboration among students (Wajnryb, 1990;Willis & Willis, 2007). Collaborative tasks entail crucial benefits for L2 learners, as they require interaction that provokes language production (see Sousa, Tiraboschi, Lago, & Figueiredo, 2019 for the importance of collaborative tasks in L2 learning). Through the interaction learners can notice certain features in the input, which can facilitate the learning process of new information (see Schmidt, 1990 for the Noticing Hypothesis).…”
Section: Group Dictationmentioning
confidence: 99%